(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Impulse purchase or motivation buy is a simply buy, where the choice to purchase an item is made only a moment before the genuine buy is done and it isn’t pre-arranged. Online retailers are in an exceptional position since they can get to a client whenever through content, email, shows promotions, and web-based social networking. Web based life is one primary factor in all by which a retailer have in position to impact the clients and raising the motivation purchasing. Technology enables customer to explore items to name them and reprimand them in level with measure, and the sky is the limit from there. Subsequently numerous organizations today have pages on interpersonal organizations to supplement the data held about items, held by the input of buyers about items and have a tendency to relate more to an organization in the wake of perusing different surveys. The objective of paper is related to the role of social media marketing factors and their impact on Impulse buying behavior. Consumer behavior, therefore it has been made a quantitative research and on the other side regression is used as a tool because impact has checked on one factor because of other. One way ANOVA also used to check the mean differences. The sample counted 112 respondents and from the statistical perspective, the conclusions were established in terms of the univariate and bivariate analysis. Following the analysis of the research variables we can make a consumer profile that uses social networks. Likewise, after doing the complex statistical analysis using tools and the analysis offered by the online platform the host of structured questionnaire. In findings it is clear that social media marketing factors impact on impulse buying directly now days. Unplanned purchase increases due to social media marketing and up to 40 percent extra expenses increases due to the social media factors.